Kathryn “Kitsie” Emerson Sebagai Pelopor Penerjemahan Secara Simultan Pertunjukan Wayang Kulit (2005-2023) - Sari, Setiani Novita; Puguh, Dhanang Respati; Hartatik, Endah Sri (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This study examines Kathryn “Kitsie” Emerson’s role as a pioneer of simultaneous or spontaneous translation in wayang kulit performances from 2005 to 2023. The purpose of this study is to analyze Kathryn “Kitsie” Emerson’s strategy as a pioneer in simultaneous translation in wayang kulit performances. This research uses the historical method by collecting sources through in-depth interviews and related documents. The results of this study describe Kathryn “Kitsie” Emerson’s journey in studying wayang kulit performances to when she discovered and developed a strategy for simultaneous translation of wayang kulit performances for puppeteers performing in Indonesia and abroad. Kathryn “Kitsie” Emerson is a practitioner of Surakarta Javanese karawitan and a simultaneous translator of wayang kulit performances. She is from the United States. Kathryn “Kitsie” Emerson’s simultaneous translation strategy helps foreigners to understand live wayang kulit performances. However, Kathryn “Kitsie” Emerson’s role as a simultaneous interpreter of wayang kulit performances has never been discussed in any research. This study shows that Kathryn “Kitsie” Emerson’s strategy of simultaneous translation of wayang kulit performances has played a role in the dissemination of Javanese traditional performing arts to foreign countries.